Cyan / blue light quantum confined CsPbBr3 composite material and its preparation method and application

By using post-synthetic tailoring and in-situ encapsulation methods containing aminosilane coupling agent and polymethylhydrosiloxane, a high fluorescence quantum yield and high stability cyan/blue quantum confined domain CsPbBr3 composite material was prepared, and the solution was solved The problems of high material stability and preparation cost in the prior art have achieved efficient and stable quantum bound domain effects.

CN118772879BActive Publication Date: 2025-02-14ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411262157.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-02-14
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

It is difficult to prepare cyan/blue quantum confined domain CsPbBr3 composite materials with high fluorescence quantum yield and high stability, and the preparation process is high and the material is unstable.

Method used

Using aminosilane-containing coupling agent and polymethylhydrosiloxane, quantum confined domain CsPbBr3 composite materials with adjustable fluorescence wavelengths were prepared by post-synthetic tailoring and in-situ packaging.

Benefits of technology

A high quantum efficiency (PLQY remains above 80%) and high stability cyan/blue light quantum confined domain CsPbBr3 composite material is achieved, reducing the preparation cost and achieving the quantum confined domain effect in normal temperature and air environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118772879B_ABST
    Figure CN118772879B_ABST
Patent Text Reader

Abstract

The invention discloses a cyan / blue light quantum confined CsPbBr 3 Composite material and preparation method and application thereof, the preparation method of the material comprises: preparing CsPbBr 3 Nanocrystal dispersion, in air environment, under stirring conditions, is introduced into CsPbBr 3 An amino-containing silane coupling agent was added to the nanocrystal dispersion to tailor its structure and obtain quantum-confined CsPbBr 3 colloidal solution, and the addition of polymethylhydrogensiloxane to quantum confined CsPbBr 3 The method is simple in preparation conditions and easy to obtain raw materials. The obtained quantum confined CsPbBr 3 The fluorescence wavelength of the composite material can be arbitrarily adjusted in the cyan and blue light regions, with high quantum yield and good stability. It has application prospects in full-spectrum lighting, optical communication, full-color display and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of semiconductor optoelectronic materials, and specifically relates to a cyan / blue light quantum confined CsPbBr with high fluorescence quantum yield and high stability. 3 Composite materials and their preparation methods and applications. Background Art

[0002] All-inorganic perovskite nanocrystals (CsPbX 3 , X = Cl, Br, I) show great application potential in optoelectronic devices such as light-emitting diodes, solar cells, photodetectors, lasers, etc. due to their excellent optical properties, such as high photoluminescence quantum yield (PLQY), good emission purity, wide emission range, and low material cost.

[0003] At present, there are a large number of technical routes for the preparation of efficient and stable green or red fluorescent all-inorganic nanocrystals (such as CsPbBr 3 and CsPbI 3 However, the development of cyan / blue fluorescent perovskite nanocrystals lags behind significantly, and cyan / blue luminescent components are indispensable in full-spectrum lighting, optical communications, and full-color display. In the prior art, there are two methods for preparing cyan / blue luminescent perovskite nanocrystals: component engineering and dimension engineering. Component engineering mainly controls the size of mixed halide perovskite nanocrystals (CsPbCl X Br 3-X ) to achieve cyan / blue fluorescence, but Cl and Br elements will phase separate under electric field or light stimulation, resulting in spectral shift; the key to dimensional engineering is to convert CsPbBr 3 The quantum confinement of CsPbBr is obtained by reducing one dimension or the overall size of the nanocrystal to below its exciton Bohr radius. 3 Nanocrystals fundamentally avoid the spectral instability caused by phase separation. However, these quantum confined nanocrystals usually have a large surface area to volume ratio, resulting in high defect density, low PLQY, and easy aggregation, resulting in spectral red shift.

[0004] In order to achieve bright and stable cyan / blue fluorescence emission, an appropriate matrix should be selected to suppress the self-aggregation of quantum confined perovskite nanocrystals and protect them from environmental stimuli such as polar molecules, heat and light. Based on this, the existing technical routes mostly use porous materials such as mesoporous silica (Angew. Chem. Int. Ed. 2018, 57, 8881), molecular sieves (Mater. Horiz., 2023, 10, 5079) and mesoporous alumina to in situ grow and stabilize quantum confined CsPbBr 3The independent nanospaces in the porous matrix can act as templates to restrict and separate the growth of perovskite nanoparticles, thus achieving quantum confinement effects. However, these porous templates are usually prepared by high-temperature calcination (more than 500 °C). o C) obtained, which enables the preparation of quantum confined CsPbBr 3 The cost of composite materials is extremely high. In addition, the porous structure is difficult to resist the penetration of polar molecules for a long time, which is not conducive to the quantum confinement of CsPbBr 3 Long-term stability.

[0005] The invention adopts amino silane coupling agent and polymethylhydrogensiloxane, obtains quantum confined CsPbBr with adjustable fluorescence wavelength in cyan and blue regions, high quantum efficiency and high stability through post-synthesis tailoring and in-situ encapsulation. 3 Composite materials can be widely used in full-spectrum lighting, optical communications, full-color display and other fields. Summary of the invention

[0006] In order to overcome the shortcomings and deficiencies in the above-mentioned prior art, the present invention provides a cyan / blue light quantum confined CsPbBr 3 Composite materials and their preparation methods and applications.

[0007] The technical solution of the present invention is as follows:

[0008] A cyan / blue light quantum confined CsPbBr 3 The method for preparing the composite material comprises the following steps:

[0009] (1) Synthesis of CsPbBr 3 Nanocrystals, dispersed in organic solvents, obtained CsPbBr 3 Nanocrystal dispersion;

[0010] The organic solvent is selected from toluene, ethyl acetate, dichloromethane or n-hexane;

[0011] The obtained CsPbBr 3 In the nanocrystal dispersion, CsPbBr 3 The mass fraction of nanocrystals is 1-2%, preferably 1-1.5%;

[0012] Cb 3 The nanocrystals have green fluorescence and can be synthesized by known methods, such as high temperature hot injection method (Nano Lett., 2015, 15, 3692), ligand-assisted reprecipitation method (Adv. Funct. Mater., 2016, 26,2435) or emulsion synthesis method (ACS Appl. Mater., Interfaces 2015, 7, 28128);

[0013] (2) In an air environment and under stirring conditions, add the CsPbBr obtained in step (1) to 3 Amino silane coupling agent and polymethylhydrogensiloxane are added to the nanocrystal dispersion, and the mixture is stirred for 0.5 to 2 h, and then centrifuged. The resulting precipitate is dispersed in an organic solvent again, and after a second centrifugation, the precipitate is collected and vacuum dried to obtain the cyan / blue light quantum confined CsPbBr 3 Composite materials (powder form);

[0014] Amino silane coupling agent and CsPbBr 3 The molar ratio of Pb in the nanocrystals is 20-80:1;

[0015] The volume ratio of polymethyl hydrogen siloxane to amino-containing silane coupling agent is 1 to 4:1;

[0016] The amino-containing silane coupling agent is selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 2-aminoethylaminomethyltriethoxysilane, 3-(2-aminoethyl)-aminopropyltriethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, 11-aminoundecyltriethoxysilane, 4-anilinotriethoxysilane, preferably 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane;

[0017] The ambient temperature and relative humidity of the continuous stirring environment are 10~40 o C, 20~80%, preferably 15~30 o C. 30~60%;

[0018] The definition of organic solvent is the same as in step (1);

[0019] During centrifugation, the speed is 3000~8000 rpm and the centrifugation time is 5~10 minutes;

[0020] Vacuum drying temperature 30~70 o C, time 2~10 h, preferably temperature 40~60 o C, time 4~6 h.

[0021] The present invention relates to cyan / blue light quantum confined CsPbBr prepared by the above preparation method 3 Composite materials.

[0022] The cyan / blue light quantum confinement CsPbBr 3 Composite materials can be used in full-spectrum lighting, optical communications, full-color display and other fields.

[0023] The technical principles of the present invention are as follows:

[0024] The present invention adopts a top-down strategy to first synthesize CsPbBr 3 nanocrystals, and then to CsPbBr 3 The amino-containing silane coupling agent was introduced into the nanocrystal dispersion and used to couple with CsPbBr 3 The strong interaction of the lattice has an important effect on the CsPbBr 3 The nanocrystals are "cut" to reduce their size to achieve the quantum confinement effect; and the luminescent color can be regulated in the cyan and blue regions by changing the molar ratio of the amino-containing silane coupling agent to Pb. At the same time, the alkoxy group at the end of the silane coupling agent will undergo a hydrolysis reaction driven by trace amounts of water in the solvent and air to form silanol groups. The silanol groups react with hydrogen-containing silicone oil to form a polymer network in situ to confine the quantum confinement CsPbBr 3 The nanoparticles are separated from each other, inhibiting their aggregation, while the polymer network acts as an encapsulation, blocking the external environment from the quantum confined CsPbBr 3 of erosion.

[0025] The advantages and beneficial effects of the present invention are:

[0026] (1) The present invention does not require high temperature or special equipment, and can achieve quantum confinement of CsPbBr at room temperature and in an air environment. 3 The raw materials for the preparation of composite materials are common and easily available.

[0027] (2) The present invention uses an amino-containing silane coupling agent to couple green fluorescent CsPbBr 3 The quantum confined CsPbBr was obtained by tailoring the structure of nanocrystals. 3 The fluorescence wavelength of the composite material can be adjusted arbitrarily in the cyan and blue light regions, and the emission line width is only 15nm. 3 The passivation effect keeps its quantum yield above 80%.

[0028] (3) The present invention utilizes the cross-linking reaction of hydrogenated silicone oil and silane coupling agent to form a polymer network to quantum confine CsPbBr 3 In-situ encapsulation significantly improves its stability against polar solvents, heat and ultraviolet light. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 : Quantum confined CsPbBr prepared in Example 1 3 Fluorescence spectra and physical images of the composite materials.

[0030] Figure 2 : Quantum confined CsPbBr prepared in Example 2 3 Fluorescence spectra and physical images of the composite materials.

[0031] Figure 3 : Quantum confined CsPbBr prepared in Example 3 3 Fluorescence spectra and physical images of the composite materials.

[0032] Figure 4 : Quantum confined CsPbBr prepared in Example 4 3 Fluorescence spectra and physical images of the composite materials.

[0033] Figure 5 : CsPbBr prepared in Comparative Example 1 3 Fluorescence spectrum and physical picture of nanocrystals.

[0034] Figure 6 : Quantum confined CsPbBr prepared in Example 3 3 Composite material and CsPbBr prepared in Comparative Example 1 3 Transmission electron microscopy image of nanocrystals.

[0035] Figure 7 : Quantum confined CsPbBr prepared in Example 3 3 Composite material and CsPbBr prepared in Comparative Example 1 3 Changes in fluorescence intensity of nanocrystals over time under conditions of polar solvent immersion (a), thermal aging (b), and UV irradiation (c).

[0036] Figure 8 : Actual picture of the composite material powder prepared in Comparative Example 2.

[0037] Fig. 9 : X-ray diffraction patterns of the composite materials prepared in Example 3 and Comparative Example 2. DETAILED DESCRIPTION

[0038] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0039] Embodiment 1:

[0040] Add 1.47 g PbBr into a 100 mL three-necked flask. 2 , 10 mL oleic acid, 10 mL oleylamine and 40 mL 1-octadecene were stirred under vacuum at 120 °C. o The reaction was carried out at 30 min and then the temperature was raised to 180 o C, quickly inject 2 mL of cesium oleate (11wt%, solvent is octadecene (ODE), the same below), react for 10 s, take it out, and cool it to 0 oC, the reaction solution was placed in a centrifuge tube, 20 mL of ethyl acetate was added, and the mixture was centrifuged at 8000 rpm for 10 min. The precipitate was then dispersed in toluene and centrifuged again at 6000 rpm for 10 min. The supernatant was taken to obtain CsPbBr 3 The nanocrystal dispersion was diluted to a concentration of 1.5 wt % for later use.

[0041] Take the above CsPbBr 3 To 2 mL of nanocrystal dispersion, 100 μL of 3-aminopropyltriethoxysilane and 200 μL of polymethylhydrogensiloxane were added in sequence under vigorous stirring. o C and 50% humidity for 2 h, then the reaction solution was centrifuged at 5000 rpm for 10 min, the resulting precipitate was dispersed in toluene again, centrifuged a second time (5000 rpm, 10 min) and then centrifuged at 60 o C was vacuum dried for 5 h to obtain quantum confined CsPbBr 3 Composite material powder, its fluorescence spectrum and physical picture are as follows Figure 1 As shown, the PLQY is 84%.

[0042] Embodiment 2:

[0043] 0.04 g PbBr 2 , 0.05 g CsBr was dissolved in 2 mL DMF, 200 μL oleic acid and 100 μL oleylamine were added, and the mixture was uniformly mixed to form a precursor solution. 5 mL toluene was taken, stirred vigorously, and 200 μL of the precursor solution was quickly injected, followed by 2 mL ethyl acetate, centrifuged at 9000 rpm for 9 min, and the precipitate was dispersed in 5 mL toluene again, centrifuged at 5000 rpm for 9 min, and the supernatant was collected to obtain CsPbBr 3 The nanocrystal dispersion is diluted to a concentration of 1wt% for later use.

[0044] Take the above CsPbBr 3 To 2 mL of the nanocrystal dispersion, 250 μL of 3-(2-aminoethyl)-aminopropyltrimethoxysilane and 500 μL of polymethylhydrogensiloxane were added in sequence under vigorous stirring. o C and 50% humidity for 2 h, then the reaction solution was centrifuged at 8000 rpm for 10 min, the resulting precipitate was dispersed in toluene again, centrifuged a second time (8000 rpm, 10 min) and then centrifuged at 50 o C was vacuum dried for 8 h to obtain quantum confined CsPbBr 3 Composite material powder, its fluorescence spectrum and physical picture are as follows Figure 2As shown, the PLQY is 82%.

[0045] Embodiment 3:

[0046] Add 1.47 g PbBr into a 100 mL three-necked flask. 2 , 10 mL oleic acid, 10 mL oleylamine and 40 mL 1-octadecene were stirred under vacuum at 120 °C. o The reaction was carried out at 30 min and then the temperature was raised to 180 o C, quickly inject 4 mL of cesium oleate, react for 10 s, take it out, put it in an ice water bath to cool to room temperature, put the reaction solution in a centrifuge tube, add 20 mL of ethyl acetate, centrifuge at 8000 rpm for 10 min, then disperse the precipitate in dichloromethane, centrifuge it again at 6000 rpm for 10 min, take the supernatant, and obtain CsPbBr 3 The nanocrystal dispersion is diluted to a concentration of 2wt% for later use.

[0047] Take the above CsPbBr 3 2 mL of nanocrystal dispersion was added with 300 μL of 3-aminopropyltriethoxysilane and 900 μL of polymethylhydrogensiloxane in sequence under vigorous stirring. o C and 50% humidity for 2 h, then the reaction solution was centrifuged at 5000 rpm for 10 min, the resulting precipitate was dispersed in dichloromethane again, centrifuged a second time (5000 rpm, 10 min) and then centrifuged at 40 o C vacuum drying for 6 h to obtain quantum confined CsPbBr 3 Composite material powder, its fluorescence spectrum and physical picture are as follows Figure 3 As shown, the PLQY is 79%.

[0048] Embodiment 4:

[0049] 0.06 g PbBr 2 , 0.08 g CsBr was dissolved in 4 mL DMF, 300 μL oleic acid and 200 μL oleylamine were added, and the mixture was uniformly mixed to form a precursor solution. 5 mL toluene was taken, stirred vigorously, and 250 μL of the precursor solution was quickly injected, followed by 2 mL ethyl acetate, centrifuged at 9000 rpm for 9 min, and the precipitate was dispersed in 5 mL toluene again, centrifuged at 5000 rpm for 9 min, and the supernatant was collected to obtain CsPbBr. 3 The nanocrystal dispersion is diluted to a concentration of 1wt% for later use.

[0050] Take the above CsPbBr 3To 2 mL of the nanocrystal dispersion, 350 μL of 3-aminopropyltrimethoxysilane and 700 μL of polymethylhydrogensiloxane were added in sequence under vigorous stirring. o C and 70% humidity for 0.5 h, then the reaction solution was centrifuged at 7000 rpm for 10 min, the resulting precipitate was dispersed in toluene again, centrifuged a second time (7000 rpm, 10 min) and then centrifuged at 60 o C was vacuum dried for 6 h to obtain quantum confined CsPbBr 3 Composite material powder, its fluorescence spectrum and physical picture are as follows Figure 4 As shown, the PLQY is 78%.

[0051] Comparative Example 1:

[0052] Referring to Example 3, except that 3-aminopropyltriethoxysilane was not added, the other preparation processes and conditions were the same as those in Example 3 to obtain CsPbBr 3 Nanocrystals, their fluorescence spectra and physical pictures are as follows Figure 5 As shown, the PLQY is 86%.

[0053] Figure 6 The quantum confined CsPbBr prepared in Example 3 3 Composite material and CsPbBr prepared in Comparative Example 1 3 Transmission electron microscopy (TEM) image of nanocrystals, Figure 6 It can be seen that amino silane coupling agents can 3 Nanocrystals are "trimmed" to reduce their size to achieve the quantum confinement effect.

[0054] Figure 7 The quantum confined CsPbBr prepared in Example 3 3 Composite material and CsPbBr prepared in Comparative Example 1 3 Nanocrystals were immersed in polar solvents and thermally aged (70 o C) and the change of fluorescence intensity under ultraviolet light conditions, Figure 7 It can be seen that the quantum confined CsPbBr 3 The stability of the composite material is significantly stronger than that of CsPbBr 3 Nanocrystals.

[0055] Comparative Example 2:

[0056] Referring to Example 3, the difference is that polymethylhydrogensiloxane is not added, and the other preparation processes and conditions are the same as those of Example 3. The actual picture of the obtained composite material powder is as follows: Figure 8 As shown, there is no obvious fluorescence emission under UV light excitation.

[0057] Fig. 9The X-ray diffraction (XRD) diagrams of the composite materials prepared in Example 3 and Comparative Example 2 are shown in FIG. Fig. 9 It can be seen that the perovskite nanocrystals in the composite material prepared in Example 3 are CsPbBr 3 In the composite material prepared in Comparative Example 2, CsPbBr 3 Transformed into Cs 4 PbB 6 , indicating that the addition of polymethylhydrogensiloxane can inhibit the quantum confinement of CsPbBr 3 phase change.

Claims

1. A method for preparing a cyan / blue light quantum confined CsPbBr3 composite material, characterized in that: The steps include: (1) synthesizing CsPbBr3 nanocrystals and dispersing them in an organic solvent to obtain a CsPbBr3 nanocrystal dispersion; The mass fraction of CsPbBr3 nanocrystals in the obtained CsPbBr3 nanocrystal dispersion is 1-2%; The organic solvent is selected from toluene, ethyl acetate, dichloromethane or n-hexane; (2) in an air environment and under stirring conditions, adding an amino silane coupling agent and polymethylhydrogensiloxane to the CsPbBr3 nanocrystal dispersion obtained in step (1), stirring for 0.5 to 2 h, and then centrifuging. The obtained precipitate is dispersed again in an organic solvent, and after a second centrifugation, the precipitate is collected and vacuum dried to obtain the cyan / blue light quantum confined CsPbBr3 composite material; The molar ratio of the amino-containing silane coupling agent to Pb in the CsPbBr3 nanocrystals is 20-80:1; The volume ratio of polymethyl hydrogen siloxane to amino-containing silane coupling agent is 1 to 4:1; The amino-containing silane coupling agent is selected from one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-(2-aminoethyl)-aminopropyltrimethoxysilane; The ambient temperature and relative humidity of the continuous stirring were 15~30 o C. 30~60%; The organic solvent is selected from toluene, ethyl acetate, dichloromethane or n-hexane.

2. The method for preparing the cyan / blue light quantum confined CsPbBr3 composite material as claimed in claim 1, characterized in that: In step (2), during centrifugation, the rotation speed is 3000-8000 rpm and the centrifugation time is 5-10 minutes.

3. A cyan / blue light quantum confined CsPbBr3 composite material obtained by the preparation method as described in any one of claims 1 to 2.

4. Application of the cyan / blue light quantum confined CsPbBr3 composite material as described in claim 3 in full-spectrum lighting, optical communication, and full-color display.

Citation Information

Patent Citations

  • Perovskite composite material and preparation method thereof

    CN109837084A

  • Synthesis method of super-hydrophobic perovskite nanocrystal luminescent composite material

    CN114426840A